Multiplex cytokine analyses in patients with rheumatoid arthritis require use of agents blocking heterophilic antibody activity. (2nd January 2017) - Olsson, P; Theander, E; Bergström, U; Jovinge, S; Jacobsson, LTH; Turesson, C
Abstract : Objectives : Heterophilic antibodies, such as rheumatoid factor (RF), are known to interfere with enzyme-linked immunosorbent assays (ELISAs). Treatment of rheumatoid arthritis (RA) with tumour necrosis factor (TNF)-α blockers is well established. The aims of this study were to develop a protocol for blocking the interaction of present heterophilic antibodies and to validate this procedure by evaluating the effect on correlations of cytokine levels to clinical response in RA patients treated with adalimumab. Method : Fourteen patients with active RA were evaluated at baseline and 3 months after starting adalimumab treatment. Cytokines were analysed with a commercial 12-plex bead ELISA. To block interference by RF, a commercial blocker (HeteroBlock) was used. To determine the optimal concentration of HeteroBlock, patient sera were analysed with different concentrations of HeteroBlock. Subsequently, baseline and follow-up sera from the 14 patients were analysed and correlated with clinical outcome. Results : Measured cytokine levels were reduced in the majority of samples when adding the blocker. The optimal concentration of HeteroBlock was 1600 μg/mL of serum. Sera with high RF levels were more prone to produce false positive values, although some RF-negative sera also demonstrated evidence of interference. HeteroBlock did not interfere with the analysis. In RA patients treated with adalimumab, changes in interleukin (IL)-6 levels between baseline and follow-up correlated with changes in erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) in sera with added HeteroBlock. Conclusions : When analysing sera from patients with RA with multiplex bead ELISA, the assay should be evaluated for interference by heterophilic antibodies, and if present corrected with, for example, HeteroBlock.